SOSIALISASI HEALTH PROMOTING SCHOOL PADA SEKOLAH TINGKAT PAUD, SD, SMP DAN SMA DI WILAYAH KERJA PUSKESMAS KASANG PUDAK KABUPATEN MUARO JAMBI - Reskiaddin, La Ode; Ibnu, Ismi Nurwaqiah; Sari, Rumita Ena; Mariana, Anni Tiurma (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2023)
Health problems in school settings are quite complex. If these health problems are not addressed, it will have an impact on the health of students and school residents. One of the efforts that can be made to overcome and prevent these problems is by implementing healthy schools. The purpose of this service is to socialize Health Promoting School at preschool, elementary, middle and high school level in the Kasang Pundak Health Center Working Area, Muaro Jambi Regency. The intervention carried out in this service is in the form of socialization or education related to healthy campuses. The targets in this service are 34 school principals in the public health service of Kasang Pundak working area. The results of the analysis show that the average difference in knowledge before and after socialization regarding health promoting school values with a Z-table value of -1.645 with alpha 0.05. In addition, support was obtained by all schools and several stakeholders in realizing healthy schools through the signing of a joint commitment. The need for continuous assistance and monitoring by health center personnel in realizing healthy schools.